Severe COVID-19 during pregnancy and the subsequent premature delivery (2020)
Coronavirus disease 2019 (COVID-19), which is caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was declared a pandemic in January 2020. Although most of the cases in pregnant women are mild, there are reports of increasing severe infection in pregnancy. Only a few case of SARS-CoV-2 infection in preterm neonates delivered by mothers with COVID-19 have been reported till date. The possibility of in utero transmission of SARS-CoV-2 is highly controversial. 1,2 While SARS-CoV-2 has been detected in several neonates by reverse transcriptionpolymerase chain reaction (RT-PCR ) of nasopharyngeal swabs collected in the early hours or days of life,3,4 the reliability of these swabs is under scrutiny, as there is a chance of contamination by coronavirus-infected maternal body fluids.